"Historia est magistra vitae"? The impact of historical victimhood on current conspiracy beliefs. (February 2022) - Pantazi, Myrto; Gkinopoulos, Theofilos; Witkowska, Marta; Klein, Olivier; Bilewicz, Michal
Conspiracy beliefs constitute a propensity to attribute major events to powerful agents acting against less powerful "victims". In this article we test whether collective victimhood facilitates conspiracy thinking. Study 1 showed that perceived group victimhood is associated with generic and group-specific conspiracy beliefs, but only for individuals who identify highly with their ingroup. Study 2 employed an experimental design to show that experimentally increased group victimhood leads to increased endorsement of conspiracy beliefs among high ingroup identifiers, but decreases endorsement of conspiracy beliefs among low identifiers. This effect was mediated by lack of trust towards outgroup members. Study 3 sought to replicate Study 2 in a different socio-political context. While Study 3 did not directly support the relationship between victimhood, group identification and conspiracy beliefs, an integrated meta-analysis of all three studies provides evidence for a significant interaction of victimhood and group identification in predicting conspiracy beliefs.